"A dismantled society": meta-synthesis of the phenomenon of violence in indigenous populations - Berenice Juan-Martínez; Lubia del Carmen Castillo-Arcos; Leticia Cortaza-Ramírez (Universidade Federal do Rio Grande do Sul, 2018)
Abstract OBJECTIVE To analyze publications of qualitative studies that addressed the phenomenon of violence in indigenous population. METHOD Meta-synthesis of studies published in the period of 2006 to 2016, with search in the Ebsco Host, Cuiden Plus, Science Direct, Springer, and Web of Science databases. RESULTS A new reinterpretation of the findings was generated from the codes and categories of the primary articles. Five categories emerged: living violence, factors associated with patterns of violence, consequences of violence, interaction dynamics in situations of violence, and how to deal with violence. CONCLUSIONS Indigenous people experience different types of violence at an early age; experienced in the family. This makes it an emerging social problem that must be taken care of urgently and represents an area of opportunity for the nursing professionals whose central focus is human care.